Automatic motor vehicle number plate recognition - Saha, Krishno; Ishrak, Parvez; Shovon, Jahid Hossian; Abir, Alinur Rahman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.